The Unheard Voices of Teenage Mothers in Public Senior High Schools in Ghana - Gyasi, Ficus (IJRDO- Journal of Educational Research, 2020)
This qualitative study explores the experiences of teenage mothers in public senior high schools (SHSs) in Ghana. Using a purposive sampling technique, eighteen (18) participants, comprising fourteen (14) teenage mothers in senior high schools (SHSs), two (2) Heads of public SHS and two (2) Guidance and Counselling Coordinators (School Counsellors) were sampled. With semi-structured interview guide, data was collected through face-to-face interview and analysed using thematic analysis. The findings were experiences of rejection, abuse, discrimination and stigmatization from peer students, and teachers. It emerged that the ripple effects of these experiences on the teenage mothers included depression, isolation and low grades. Also, the results indicated that the teenage mothers employed an internal locus control, and divine intervention. In order for teenage mothers to succeed with their schooling, a clear state policy on teenage mothers’ school re-entry, integration and completion is needed, as well as maximum support from all stakeholders - school authorities, educators, parents, peers and the entire community. It is necessary that public SHSs in the country establish well-structured guidance and counselling programmes so that teenage mothers can access the needed counselling support.